Application of quantitative light-induced fluorescence to determine the depth of demineralization of dental fluorosis in enamel microabrasion: a case report - Tae-Young Park; Han-Sol Choi; Hee-Won Ku; Hyun-Su Kim; Yoo-Jin Lee; Jeong-Bum Min (Korean Academy of Conservative Dentistry, 2016)
Enamel microabrasion has become accepted as a conservative, nonrestorative method of removing intrinsic and superficial dysmineralization defects from dental fluorosis, restoring esthetics with minimal loss of enamel. However, it can be difficult to determine if restoration is necessary in dental fluorosis, because the lesion depth is often not easily recognized. This case report presents a method for analysis of enamel hypoplasia that uses quantitative light-induced fluorescence (QLF) followed by a combination of enamel microabrasion with carbamide peroxide home bleaching. We describe the utility of QLF when selecting a conservative treatment plan and confirming treatment efficacy. In this case, the treatment plan was based on QLF analysis, and the selected combination treatment of microabrasion and bleaching had good results.